Numerical Simulation of Hybrid Electric–Structural Control for Microdroplet Formation in Ribbed T-Junction Microchannels - Ruyi Fu (Micromachines, 2025)
Microdroplet formation in microfluidic systems plays a pivotal role in chemical engineering, biomedicine, and energy applications. Precise control over the droplet size and formation dynamics of microdroplets is essential for optimizing performance in these fields. This work explores a hybrid control strategy that combines an active electric field with passive rib structures to regulate the droplet formation in a ribbed T-junction microchannel under an electric field. Numerical simulations based on the phase-field method are employed to analyze the effects of the electric capillary number <semantics>Cae</semantics> and rib height <semantics>a/wc</semantics> on the droplet formation mechanism. The results reveal that increasing <semantics>Cae</semantics> induces three distinct flow regimes of the dispersed phase: unpinning, partially pinning, and fully pinning regimes. This transition from an unpinning to a pinning regime increases the contact area between the wall and dispersed phase, restricts the flow of the continuous phase, and induces the shear stress of the wall, leading to a reduction in droplet size with the enhanced <semantics>Cae</semantics>. Furthermore, an increase in rib height <semantics>a/wc</semantics> enhances the shear stress of the continuous phase above the rib, causing a progressive shift from a fully pinning to an unpinning regime, which results in a linear decrease in droplet size. A new empirical correlation is proposed to predict droplet size <semantics>S/<msubsup>wc2</msubsup></semantics> as a function of rib height <semantics>a/wc</semantics> and two-phase flow rate ratio <semantics>Qd/Qc</semantics>: <semantics>S/<msubsup>wc2</msubsup>=(−0.62−1.8Qd/Qc)(a/w)+(0.64+0.99Qd/Qc)</semantics>.